2022
DOI: 10.1088/1361-6544/ac619f
|View full text |Cite
|
Sign up to set email alerts
|

Equivariant bifurcation, quadratic equivariants, and symmetry breaking for the standard representation of S k

Abstract: Motivated by questions originating from the study of a class of shallow student-teacher neural networks, methods are developed for the analysis of spurious minima in classes of gradient equivariant dynamics related to neural networks. In the symmetric case, methods depend on the generic equivariant bifurcation theory of irreducible representations of the symmetric group on k symbols, S k ; in particular, the standard representation of S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
(112 reference statements)
0
2
0
Order By: Relevance
“…As mentioned, in [9], it was shown that, empirically, the isotropy groups of spurious minima are large subgroups of S d × S d and so are symmetry breaking. Below, we outline the framework of symmetry breaking [17,11,27,28,16,29] allowing the analytic results given for the associated non-convex optimization landscape. The methods are first illustrated with reference to the simplest S d × S d -isotropy case, assuming the Frobenius norm, and are later described for general isotropy groups and tensor norms.…”
Section: Symmetry Breaking and Families Of Critical Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, in [9], it was shown that, empirically, the isotropy groups of spurious minima are large subgroups of S d × S d and so are symmetry breaking. Below, we outline the framework of symmetry breaking [17,11,27,28,16,29] allowing the analytic results given for the associated non-convex optimization landscape. The methods are first illustrated with reference to the simplest S d × S d -isotropy case, assuming the Frobenius norm, and are later described for general isotropy groups and tensor norms.…”
Section: Symmetry Breaking and Families Of Critical Pointsmentioning
confidence: 99%
“…In [16], it is proved that adding neurons can turn symmetric spurious minima into saddles; minima of lesser symmetry require more neurons. In [29], generic S d -equivariant steady-state bifurcation is studied, emphasizing the complex geometry of the exterior square and the standard representations along which spurious minima studied in [16] are created and annihilated. 1.3.…”
Section: Introductionmentioning
confidence: 99%